IMPLEMENTASI KEBIJAKAN PENGELOLAAN BADAN USAHA MILIK DESA DI DESA TONDEGESAN KECAMATAN KAWANGKOAN - LIOW, HAPPY; LENGKONG, FLORENCE DAICY; PALAR, NOVIE ANDERS (Sam Ratulangi University, 2018)
Tondegesan Village Government established BUMDes as a body that professionally managed to manage village assets and became the motor of the economy of rural communities, but because BUMDes was the first business entity to operate in Tondegesan Village, there were several problems, such as the lack of human resources having competence in managing business entities, and lack of funding and facilities used to support BUMDes programs. The purpose of this research is to know how the implementation of Village Owned Enterprise (BUMDes) Program in Tondegesan Village, Kawangkoan Sub-district. This study uses the implementation theory of Edward III which focuses on four dimensions in implementing policies or programs ie resources, communication, disposition, and bureaucratic structure. The method used is qualitative descriptive. Data collection techniques used were interviews, observation, literature study and documentation. The results of this study indicate that the implementation of the BUMDes program in general has been running well. This can be seen from the two main programs that have been running BUMDes well. Although in the application of standard operational procedures have not been maximal so that BUMDes programs have not run optimally, because there are some things that must be improved such as lack of competence of human resources and lack of financial resources, and lack of coordination between institutions built board BUMDes. Suggestions that can be given is by completing BUMDes' articles of association and budget, improving the quality of human resources and adding financial resources, and building coordination among institutions so that the future of cooperation between BUMDes and the Village Government can run well.Keywords: Implementation, Policy, BUMDes